LncRNA xist regulates sepsis associated neuroinflammation in the periventricular white matter of CLP rats by miR-122-5p/PKCη Axis - Wang, Huifang; Li, Yichen; Jiang, Shuqi; Liu, Nan; Zhou, Qiuping; Li, Qian; Chen, Zhuo; Lin, Yiyan; Chen, Chunbo; Deng, Yiyu (Frontiers in Immunology, 2023)
Background: Neuroinflammation is a common feature of many neurological diseases, and remains crucial for disease progression and prognosis. Activation of microglia and astrocytes can lead to neuroinflammation. However, little is known about the role of lncRNA xist and miR-122-5p in the pathogenesis of sepsis-associated neuroinflammation (SAN). This study aims to investigate the role of lncRNA xist and miR-122-5p in the pathogenesis of SAN.Methods: Levels of miR-122-5p and proinflammatory mediators were detected in the cerebrospinal fluid (CSF) of patients with intracranial infection (ICI) by ELISA and qRT-PCR. miRNA expression in the periventricular white matter (PWM) in rats was analyzed by high-throughput sequencing.Levels of lncRNA xist, miR-122-5p and proinflammatory mediators in the PWM were measured 2 using qRT-PCR and western blot. Bioinformatics analysis was used to predict the upstream and downstream of miR-122-5p. The interaction between miR-122-5p and its target protein was validated using luciferase reporter assay. BV2 and astrocytes were used to detect the expression of lncRNA xist, miR-122-5p.The level of miR-122-5p was significantly decreased in the CSF of ICI patients, while the expression of IL-1β and TNF-α were significantly upregulated. Furthermore, it was found that the expression of IL-1β and TNF-α were negatively correlated with the level of miR-122-5p. A highthroughput sequencing analysis showed that miR-122-5p expression was downregulated with 1.5fold changes in the PWM of CLP rats compared with sham group. Bioinformatics analysis found that lncRNA xist and PKCη were the upstream and downstream target genes of miR-122-5p, respectively.The identified lncRNA xist and PKCη were significantly increased in the PWM of CLP rats.Overexpression of miR-122-5p or knockdown of lncRNA xist could significantly downregulate the level of PKCη and proinflammatory mediators from activated microglia and astrocytes. Meanwhile, in vitro investigation showed that silencing lncRNA xist or PKCη or enhancing the expression of miR-122-5p could obviously inhibit the release of proinflammatory mediators in activated BV2 cells and astrocytes.LncRNA xist could regulate microglia and astrocytes activation in the PWM of CLP rats via miR-122-5p/PKCη axis, further mediating sepsis associated neuroinflammation.